Impact of educational video intervention to improve oral health knowledge and beliefs among physicians and nurses - Gaffar, Balgis Osman; Alkhaldi, Abdulrahman; Alshehri, Turki; Altayyar; Raand; Farooqi; Faraz Ahmed; Bakhurji, Eman; Virtanen, Jorma I (United Kingdom, 2025)
Background: The most prevalent dental diseases have adverse effects on an individual's general health. To address this public health crisis and oral health disparity, collaborative efforts of health professionals are critical for dental disease prevention and optimal oral health. This study evaluated the effect of an educational video intervention on oral health knowledge, beliefs, and practices of physicians and nurses.
Methods: This pre-post interventional study evaluated the immediate effects of a video-based oral health educational intervention given to nurses and physicians in Saudi Arabia. A self-administered questionnaire was distributed to participants to assess their oral health (OH) knowledge, beliefs, and practices of OH care. The study participants (physicians and nurses) were randomly exposed to two intervention groups (video or brochure) after which they responded to a post interventional survey. Means of knowledge and beliefs scores were calculated before and after the intervention. Logistic regression was applied to investigate the factors associated with good knowledge and beliefs after the educational intervention.
Results: A total of 213 healthcare providers of whom 56% were physicians participated in this study. Knowledge of OH improved significantly (p < 0.001) after the intervention and was higher among females compared to males (16.86 to 19.54). The physicians showed more improvement post intervention compared to nurses (19.76 vs. 19.30, respectively) (p < 0.001). The overall belief scores for providing OH education did not change significantly post intervention (p = 0.545). Providing OH care to the patients and conducting an OH screening increased moderately after the intervention (44.6-55.4% and 44.6-55.4%, respectively).
Conclusion: The video-based intervention was effective in improving the physicians' and nurses' knowledge, beliefs, and likelihood to incorporate OH care in their current practices. Males, Saudis, working in academia and more work experience were significantly associated with greater odds of having good knowledge after the intervention regardless of its type.
Clinical trial number: Not Applicable.